Assessment of romiplostim immunogenicity in adult patients in clinical trials and in a global postmarketing registry. (20th April 2020) - Mytych, Daniel T.; Park, Joseph K.; Kim, June; Barger, Troy E.; Boshier, Andy; Jawa, Vibha; Kuter, David J.
Summary: Antibodies to first‐generation recombinant thrombopoietin (TPO) neutralized endogenous TPO and caused thrombocytopenia in some healthy subjects and chemotherapy patients. The second‐generation TPO receptor agonist romiplostim, having no sequence homology to TPO, was developed to avoid immunogenicity. This analysis examined development of binding and neutralising antibodies to romiplostim or TPO among adults with immune thrombocytopenia (ITP) in 13 clinical trials and a global postmarketing registry. 60/961 (6·2%) patients from clinical trials developed anti‐romiplostim‐binding antibodies post‐baseline. The first positive binding antibody was detected 14 weeks (median) after starting romiplostim, at median romiplostim dose of 2 µg/kg and median platelet count of 29.5 × 10 9 /l; most subjects had ≥98·5% of platelet assessments showing response. Neutralising antibodies to romiplostim developed in 0·4% of patients, but were unrelated to romiplostim dose and did not affect platelet count. Thirty‐three patients (3·4%) developed anti‐TPO‐binding antibodies; none developed anti‐TPO‐neutralising antibodies. In the global postmarketing registry, 9/184 (4·9%) patients with spontaneously submitted samples had binding antibodies. One patient with loss of response had anti‐romiplostim‐neutralising antibodies (negative at follow‐up). Collectively, anti‐romiplostim‐binding antibodies developed infrequently. In the few patients who developed neutralising antibodies to romiplostim, there was no cross‐reactivity with TPO and no associated loss of platelet response.